Buddhist Statecraft in East Asia - Balkwill, Stephanie; Benn, James A. (Studies on East Asian Religions, 2022)
Case studies in the dynamic, contested, exciting, constant, and ever evolving relationship between Buddhism and the state across pre-modern East Asia.